Exploring potential cooperative effects in dicopper(i)-di-mesoionic carbene complexes: applications in click catalysis. Issue 1 (15th December 2015) - Hohloch, Stephan; Suntrup, Lisa; Sarkar, Biprajit
Abstract : Dicopper(i ) dimesoionic carbene complexes are active catalysts for the azide–alkyne cycloaddition reaction and are more active than their mononuclear counterparts. Abstract : Triazolylidenes are an emerging class of mesoionic carbenes with potential as ligands in homogeneous catalysis. In this contribution we present well-defined dicopper(i ) complexes with di-mesoionic carbenes where the copper centers are held at a distance of about 2.8 Å. All complexes display excellent activity as pre-catalysts for the azide–alkyne cycloaddition (click) reaction. Comparisons with analogous mononuclear complexes show the dinuclear pre-catalysts to be twice as active for the same amount of copper used. These results thus point to potentially strong cooperative effects in these dinuclear complexes, and further support the recently established dinuclear reaction pathway for the click reaction. The results presented here provide a synthetic route for generating dinuclear complexes with di-mesoionic carbenes with relatively short metal–metal distances, and opens a general platform for investigating potential cooperative effects in catalysis.